Supporting recovery from hoarding and squalor: insights from a community case study. Issue 8 (4th September 2015) - Raeburn, T.; Hungerford, C.; Escott, P.; Cleary, M.
<x xml:space="preserve">Abstract</x> Accessible summary Hoarding and squalor are more common among people with chronic mental disorders and can compromise a person's health and safety, be a public health issue and present substantial challenges to family, carers, social service agencies and clinical mental health services. This paper provides a case study outlining the complex challenges experienced by a person exhibiting hoarding and squalor behaviours, and explores the role of a mental health nurse in supporting the person towards recovery. The journey towards mental health recovery for a person with hoarding and squalor behaviours is multidynamic and requires more than clinical expertise or discreet psychotherapeutic modalities. Abstract People with hoarding behaviours acquire a large number of possessions that are often of limited or no monetary value and which they are unable or unwilling to discard. Such behaviours can substantially impair a person's ability to attend to their normal daily activities, cause substantial distress and lead to squalid living conditions. Living in squalor can compromise a person's health and safety, be a public health issue and present substantial challenges to family, carers, social service agencies and clinical mental health services. Hoarding and squalor behaviours are more common among people with co‐morbid organic and mental illness, such as developmental delay, schizophrenia, alcohol dependence and/or obsessive–compulsive disorder. This paper provides a narrative that explores the role of one Australian mental health nurse practitioner in the recovery of a person with hoarding behaviours.